Adaptability of hydraulic fracturing packers and optimization of their sealing performance for three common clastic rock reservoirs based on finite element analysis - Kang, Yusen; Long, Zhilin; Kang, Tengfang; Ren, Zhuohang; Shi, Tianzi; Zhang, Xinrui (Frontiers in Earth Science, 2022)
In this paper, the identification and structural design of the packer in hydraulic fracturing are systematically carried out, based on the finite element calculation of the contact pressure and stress distribution of the packer rubber tube in the well. Furthermore, the adaptability characteristics of the packer to 3 types of common clastic rock reservoirs (mudstone, shale, sandstone) are analyzed. Finally, the nonlinear mathematical model of the packing safety factor and the pressure under the packer under the conditions of casing, mudstone, shale and sandstone is obtained by least squares curve fitting. The results show that the maximum stress of the rubber cylinder in the three formation models of mudstone, shale and sandstone is lower than the compression set strength of the rubber cylinder, indicating that the rubber cylinder will not cause stress damage. At the same time, by analyzing the common rubber materials and constitutive models of packers, the structure of the packer rubber cylinder and a new anti-shoulder protrusion device were redesigned. Nitrile-butadiene rubber (NBR) meets the performance requirements of the rubber tube under the allowable pressure difference and temperature difference. The designed new anti-protrusion device can ensure the structural integrity and stress uniformity of the rubber tube, thereby ensuring good sealing performance. Under the three formation conditions of mudstone, shale and sandstone, the rubber cartridge can be in a safe working state, and its sealing width is close to the contact length of the rubber cartridge.  In addition, the rubber cartridge is in a good elastic deformation range. The design of the packer in this study satisfies the third strength theory and safety requirements, the deformation and sealing performance of the rubber cylinder are relatively stable, and the size of the rubber cylinder also meets the field requirements.